The Important Element Of Revenue Sharing In Arbitrate Client By Indonesian Islamic Banking Profitability - Endang Saefuddin Mubarok; Khairuddin Khairuddin; Rachmat Hidayat; Surya Adi Saputra (Kazimierz Wielki University, 2019)
This research aimed at understanding the effects of financing risk, cost efficiency, and liquidity on profitability and the impacts on profit sharing. The method used for the research was causality with purposive sampling data collection technique. The analysis model selected was the regression using panel data, namely the data repeatedly observed on the same unit of objects from time to time. The objects of the research was10 Islamic Commercial Banks in Indonesia with secondary data in the form of financial statements for 2010 - 2017 period. The results of the statistical study indicated that the NPF, OCR (BOPO), and FDR variables simultaneously influenced the profitability (ROA) with contribution value of 93.5%. Partially, the three variables had a negative and significant effect on profitability (ROA). NPF, OCR, and FDR simultaneously had a positive and significant effect on profit sharing with a contribution value of 94.53%. Partially, NPF had a negative and significant effect on profit sharing, while OCR and FDR had a positive and significant effect on profit sharing. Profitability (ROA) had a positive and significant effect on customer profit sharing. The NPF and FDR for profit sharing did not mediate their effects on profit sharing. At the same time, OCR for profit sharing through ROA, was able to mediate the OCR of the effect on profit sharing.